Introduction of continuous glucose monitoring (CGM) is a key factor in decreasing HbA1c in war refugee children with type 1 diabetes - Neuman, V; Vavra, D; Drnková, Lenka; Pruhova, S; Plachy, L; Kolouskova, S; Obermannova, B; Amaratunga, S A; Konecna, P; Vyzralkova, J; Venhacova, P; Pomahacova, R; et al. (Diabetes research and clinical practice, 2024)
AIMS: Our aim was to describe the changes in therapy and diabetes control in Ukrainian war refugee children with diabetes (CwD) during the first year of their stay in Czechia. METHODS: A total of 124 CwD (62 male, 62 female) were enrolled into this observational study. Anthropometric, laboratory and diabetes management data were acquired at baseline and at 3 months intervals for 12 months. All CwD were offered a CGM device during their first visit. Generalized Estimating Equation models were fitted in order to estimate the dynamics of studied characteristics. RESULTS: Median baseline HbA1c was 58 mmol/mol (IQR [48; 73]mmol/mol) (7.5 %, IQR[6.5;8.8]%). The HbA1c decreased significantly throughout the course of the study at a pace of - 2.2 mmol/mol (-0.2 %pt.) per visit (P = 0.01, CI[-3.2;-1.1]). The pace of the decrease in the average HbA1c was significantly higher in the group of CwD who received CGM in Czechia than in those who already had it from Ukraine by 2.9 mmol/mol (0.27 %pt.) per visit (P < 0.001, CI [-4.4; -1.3]). CONCLUSIONS: The steepest decrease in HbA1c was observed in CwD with newly initiated CGM underlining its vital role in improving the glucose control of CwD regardless of their background.
Keywords: selfmonitoring glykemie; mužské pohlaví; Male; Refugees; Continuous Glucose Monitoring; Female; Humans; Glycated Hemoglobin; diabetes mellitus 1. typu; Diabetes Mellitus, Type 1; lidé; ženské pohlaví; kontinuální monitorování glukózy; Child; dítě; glykovaný hemoglobin; uprchlíci; Blood Glucose Self-Monitoring; Blood Glucose; krevní glukóza